How Responsive are Firms to the Corporate Wealth Tax? (2019)
The corporate wealth tax is commonly associated with a non-optimal policy for fiscal revenue and efficiency. However, there is no empirical evidence regarding the behavioral response of firms to this tax. Taking advantage of the non-linearities introduced by the tax design in Colombia, this paper estimates the elasticity of corporate wealth with respect to the statutory tax rate and investigates the impact of the tax on reported assets, profits, and liabilities. Results reveal that, in years 2006 and 2010, we observe between 23.8% and 35.7% more firms at the wealth cutoffs where the tax rate changes. This implies estimated elasticities of 0.250 and 0.447 for firms with wealth around 3 billion pesos. Difference-in-differences analysis suggests that the reduction in reported wealth relates mostly to declines in assets and pre-tax profits, while no effects on liabilities are found. Absent fiscal externalities, the estimated elasticities are associated with a revenue loss and marginal deadweight loss of around 1% of fiscal revenue on the evaluated taxpayer firms. Once the negative impact on the corporate income tax is considered, these figures can be as high as 3.8%.